Wood physical and mechanical properties of Pinus canariensis grown on the dry lands in Maule’s Region, Chile - Rodríguez, Claudio; Vergara, Emilio (Bosque (Valdivia), 2008)
Physical and mechanical properties were evaluated in 46 year-old Pinus canariensis wood, growing in dry lands of Maule´s Region in Chile. The wood was conditioned to 12% moisture content and mechanical testing was according to Chilean standards. The basic density was 0.503 ± 0.03 g/cm3. The results of mechanical properties were lower compared with those gotten in Spain and Australia. Concerning Pinus radiata wood, properties were within the range or over, except for perpendicular tension strength. According to chilean standard NCh1989, P. canariensis wood is classified in ES4 group, as native woods like coigüe, laurel, lenga and roble. Because of its structural properties, according to Sallenave classifications, this species is specially appropriated for building and other structural applications.